Evaluation of the genotoxic/antigenotoxic activities of the methanolic extract of Amasonia campestris (Aubl.) Moldenke - Hapuque da Silva Souza, Keren; Azevedo do Nascimento, Alessandra; dos Santos Ribeiro, Edmara Caroline; Furtado Frazao, Gleicyanne; da Silva Brito, Natanael; da Conceição Barbosa, Sabrina; de Azevedo Bentes Monteiro Neto, Moacir (O Mundo da Saúde, 2019)
Amasonia campestris (Aubl.) Moldenke, belongs to the Lamiaceae family, found in the North, Northeast, Midwest and Southeast regions of Brazil. A. campestris tea is popularly used for the fight against malaria, diabetes among other diseases. Its common names are mendoca, macaw tail, macaw bamboo. The present study evaluated the genotoxic and antigenotoxic potential of the methanol extract of the roots of Amasonia campestris in polychromatic erythrocytes of Swiss mice. The animals were treated with different concentrations of Amasonia campestris (250, 500, 1000 and 2000 mg/kg b.w.) including positive control groups (doxorubicin, DXR 16 mg/kg body weight), negative (water) and solvent (dimethyl sulfoxide, DMSO). Concentrations were administered to the animals via a gavage as well as the negative control and solvent. The positive control was given intraperitoneally. The animals were treated daily with the respective doses for 15 days for genotoxic evaluation. after that, samples of caudal peripheral blood were collected at the hours: 24 and 48hrs after the first gavage, and on days 7 and 15. For the antigenotoxic evaluation, mice were treated on day 14 with intraperitoneal injections of DXR and caudal peripheral blood samples were collected 24 and 48hrs after this intervention. After the treatments, 2,000 polychromatic erythrocytes were counted per animal from each group to evaluate the frequency of Micronuclei. The results showed that the methanol extracts of the roots of A. campestris were not genotoxic because no statistically significant difference was observed when compared with the negative control. Animals treated with different concentrations of Amasonia campestris extracts associated with DXR had a significant reduction of micronucleated polychromatic erythrocytes when compared with the positive control. In conclusion, the methanolic extract of the roots of Amasonia campestris demonstrated antigenotoxic activity and did not prove to have genotoxic activity under the conditions used in this study.